EVALUATION OF THE IMMEDIATE EFFECT OF ANULOM VILOM PRANAYAMA ON AUTONOMIC FUNCTIONS DURING PRE-MENSTRUAL PERIOD IN YOUNG UNMARRIED FEMALES - PRIYANKA KUMARI; JYOTI ARORA; KAVITA GOYAL; NEHA SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Pre-menstrual stress (PMS), or pre-menstrual tension, comprises the recurring cyclic manifestation of a cluster of distressing physical, psychological, or behavioral alterations during the luteal phase of the menstrual cycle. Nearly, 80% of women do experience some type of pre-menstrual changes during their reproductive period. Until date, only non-pharmacological interventions, such as aerobic exercises, relaxation, and meditation are helpful in relieving pre-menstrual symptoms. Methods: During the first stage of the study, descriptive questionnaire method was used, to know the prevalence of PMS among the subjects. At the second stage, the method used was observational design and it was used before and after the yoga test. Subjects were selected for observational study based on the past menstruation period and included baseline and post-yoga tests to know the immediate effects of Anulom Vilom Pranayama on autonomic functions during the pre-menstrual period among unmarried females. The effect of Anulom Vilom Pranayama on autonomic functions in unmarried females on the PMS, health-related quality of life, and related physiological variables were examined. The statistical analysis was done by the SPSS 9 (the Statistical Package for the Social Science) software. Results: A highly significant improvement was observed in frequency domains of HRV, with an overall marked reduction in the LF/HF ratio. Significant improvement in the E/I ratio was noted after Anulom Vilom. Conclusion: The results of this study demonstrate that Anulom Vilom Pranayama training significantly improves selected variables among unmarried females. Even a single session of Anulom Vilom pranayama is beneficial in reducing PMS.